Analysis of Flow Dynamics of Carbon Monoxide Emitted from Cook Stoves in Closed Room Using CFD - Bista, Saurav Raj; Baral, Bivek; Aryal, Utsav Raj; Chaulagain, Nischal (Journal of the Institute of Engineering, 2020)
Wood being one of the major sources for cooking in developing countries has also been key for indoor air pollutions. Many studies and improvements on the stove have been conducted to enhance combustion efficiency and minimize emission. Although many Improved Cooking Stoves (ICS) programs has been widespread, due to design limitation together with operational and fuel factors have hindered the targeted emission reduction. Several studies in developing countries have shown that the even ICS have not been able to reduce the adverse impact on human health due to the use of solid biomass fuel. Despites the limitation in stove performance, alternatives have to be used to reduce the indoor air pollution till better cooking and heating system is in place in the developing countries. Proper ventilation and stove placement might be one of the few solutions. To provide an effective passive ventilation scheme, flow dynamics of the pollutants from stove to indoor space and outdoor needs to be predicted. This paper discusses about the application of Computational Fluid Dynamics (CFD) tool to predict the pollution flow pattern and dispersion dynamics with different ventilation placement and stove location. The study also considers potential thermal energy conservation in the living space with optimum ventilation.